Re:Learn: Creating a digital platform to facilitate collaborative learning on student information literacy - Borg, Linda; Eriksson, Marie-Louise (Septentrio Conference Series, 2021)
Librarians and writing tutors in higher education are working intensely to teach information literacy to students. But the extent to which this work is done collaborative or separately differs greatly between the universities. •How can we facilitate collaborative learning on questions regarding the teaching of academic information literacy? •How do we relate this teaching to various national and international frameworks and guidelines? •How do we find new ways and methods for writing tutors and librarians to work together? •Is it possible to create a platform to facilitate the exchange of ideas and tools? These are some of the questions that led us to start this project: to develop an open web course on student learning of information literacy in higher education. But instead of targeting students in higher education the target group for this course is librarians and writing tutors at Swedish universities. The project is funded by the Swedish library Association.The purpose of the course is to: •Place information literacy in an academic context, where academic writing is included together with information seeking, referencing, plagiarism etc. •Develop national cooperation on issues related to the teaching of information literacy and academic writing •To facilitate online peer learning between collegues on issues related to teaching information literacy and academic writing •Develop a platform for sharing experiences regarding tools and methods The participants will get the opportunity to participate in workshops and PBL-inspired group work on themes regarding the teaching of information literacy in higher education. In this way we hope to facilitate a creative and collaborative learning environment. The first iteration of the course will take place April-May 2021. This presentation will be about the development of the course and what we have learned so far.